Cosimo D’Amico: from the realism to hyper-realism - Giuseppina Vara (Agathón)
The Author introduces Cosimo D’Amico, a still little-known Sicilian painter whose technical mastery can be declined in heterogeneous and ever-new genres and pictorial imageries, ranging from metaphysical scenes to material landscapes, from ambiguous figures to portraits so real that they look alive.